Hitchhiking on Controlled-Release Drug Delivery Systems: Opportunities and Challenges for Cancer Vaccines - Han, Lu; Peng, Ke; Qiu, Li-Ying; Li, Meng; Ruan, Jing-Hua; He, Li-Li; Yuan, Zhi-Xiang (Frontiers in Pharmacology, 2021)
Cancer vaccines represent among the most promising strategies in the battle against cancers. However, the clinical efficacy of current cancer vaccines is largely limited by the lack of optimized delivery systems to generate strong and persistent antitumor immune responses. Moreover, most cancer vaccines require multiple injections to boost the immune responses, leading to poor patient compliance. Controlled-release drug delivery systems are able to address these issues by presenting drugs in a controlled spatiotemporal manner, which allows co-delivery of multiple drugs, reduction of dosing frequency and avoidance of significant systemic toxicities. In this review, we outline the recent progress in cancer vaccines including subunit vaccines, genetic vaccines, dendritic cell-based vaccines, tumor cell-based vaccines and in situ vaccines. Furthermore, we highlight the efforts and challenges of controlled or sustained release drug delivery systems (e.g., microparticles, scaffolds, injectable gels, and microneedles) in ameliorating the safety, effectiveness and operability of cancer vaccines. Finally, we briefly discuss the correlations of vaccine release kinetics and the immune responses to enlighten the rational design of the next-generation platforms for cancer therapy.